The Role of Environmental Management System, Environmental Performance, and Military Connections to Carbon Emission Disclosure - Felicia Destiyuanita; Dul Muid; Sugiharto (Politeknik Negeri Madiun, 2022)
This study aims to examine the role of environmental management systems, environmental performance, and military connections to the disclosure of carbon emissions. This study focuses on companies listed on the Indonesia Stock Exchange for the period 2017-2020. Hypothesis testing using multiple linear regression. Test-F shows a stable and significant model. The research results show four variables that have been proven to be insignificant to carbon emissions, namely the environmental management system, military connections, size firms, and leverage. Environmental performance and age firms in this research have affected a positive and significant impact on the disclosure of carbon emissions. This demonstrates that companies that receive the PROPER Awards from the Ministry of Environment and Forestry are those with good environmental performance in accordance with government regulations to reduce greenhouse gas emissions.